ANALISIS KINERJA BARANG MILIK NEGARA BERUPA ASET TANAH DAN BANGUNAN PADA BADAN LAYANAN UMUM UNIVERSITAS TADULAKO - Setiyono, Nanang (Katalogis, 2018)
The purpose of the study is to determine and analyze the performance of State-Owned Asset in the form of property and building assets at Tadulako University and to determine strategies to improve the asset performance. Government Regulation Number 27 of 2014 on State / Local Property Management changes the paradigm on asset management from Asset Administrator to Asset Manager. The asset managementis not only focusing on asset recording, but also in increasing non-tax revenue from asset utilization, particularly for the Public Service Agency unit. Tadulako University indicates a vertical work under the Ministry of Technology and Higher Education Research acting as a Service Agency General with a large asset ownership of property and buildings in the region of Central Sulawesi. The study applies a qualitative research. The researcher interviewedthe members who are involved in the administration and the management of State-Owned Assetin Tadulako University.Analysis of the performance of State-Owned Asset is based on the physical condition of assets, asset functionality, asset utilization and asset financial performance. The result of the study shows that the performance of State-Owned in Tadulako University is not optimal,because there are some amounts of assets indamages condition and disputes;there are unutilized assets which indicate as idle assets; and the data in the State-Ownwe Asset Report are less appropriate with the real assets condition. The utilization of State-Owned Asset in the form of property and building asset is not implemented optimally and it is not in accordance with the regulation of State-Owned Asset Management. The strategiesto improve the performance of State-Owned Assetis establishing Asset Power Proxy Unit in each Faculty, preparing assets portfolio and asset utilization through the mechanism of Operational Cooperation and Management Cooperation in accordance with the Regulation of the Minister of Finance Number 136/PMK.05/2016.